NOVAS CONFIGURAÇÕES TERRITORIAIS E RELAÇÕES INTERÉTNICAS NA AMAZÔNIA MARANHENSE: perspectivas etno-históricas acerca dos contatos entre os Ka’apor e as comunidades quilombolas - VIANA, Fernanda Lopes (2024)
This master's qualification presents an overview of the research entitled “Displacements, new territorial configurations and interethnic relations in the Maranhão Amazon: ethnohistorical perspectives on contacts between the Ka'apor and the quilombola communities", which aims to analyze the relationships between the Ka'apor indigenous population and quilombola communities located in the Gurupi microregion, in the Maranhão Amazon, in the period between the 19th and 20th centuries. The research seeks to understand how intercultural contacts affected the lives and culture of these groups, considering the cultural changes resulting from these relationships. By making use of an interdisciplinary approach, the objective is to problematize issues related to displacements, new territorial configurations and interethnic relations that occurred in this region, by sustaining the ethnohistorical perspective with insertions of history, anthropology and archeology, in an attempt to build a dialogue between them, since, without this focus, this research could not advance, in order to seek to understand the possible Afro-indigenous relationships in the Gurupi river region and the means of contact between the groups. The research is justified by the importance of understanding interethnic relations in the Maranhão Amazon and the most critical moments of struggle for territory, in situations of forced migration and displacement, addressing one of the regions that suffer the most territorial pressures in the Amazon biome of Brazil. The theoretical framework of this study was based on the studies of Agenor Pacheco (2009), which promotes the Afro-indigenous concept established in the Amazon. The methodology used is a bibliographical research, based on documental survey, with analysis of several sources, including documents, fielddiaries, theses, articles, imagery and bibliographical collections in research centers, safeguard institutions, public archives and libraries. It is important to emphasize that the research is in the development phase, therefore, it does not present results, broaddiscussions or complete final considerations, however, the fundamental argument of the theme was presented.